Gentle and lowly : the heart of Christ for sinners and sufferers - Ortlund, Dane Calvin (Wheaton, Illinois : Crossway, 2020)
"Shows how the heart of Christ feels about God's people as they sin and stumble their way through life"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Jesus Christ; God (Christianity) -- Mercy; God (Christianity) -- Love; Suffering of God